Analisa Pemilihan Saham untuk Portofolio Optimal dengan Metode Kriteria Sederhana - Mohammad Lukman; Moch. Hari (Department Industrial Engineering, University of Muhammadiyah Malang, 2002)
Generally, problem faced in making a portfolio is the large number of probabilities in risky active stock combinations available at stock market yet, if we put riskless active stock intothose combinations considering this numerous possibilities of portfolio made from stocks at stock market,a question that will arise is which portfolio to be chosen by investors. If acting rationally, the investors will chosen optimum portfolio. simple criteria method is an alternative method in forming the optimum portfolio with objective in determining stock rank in effrcient limit. This methods firstry deveroped by EltonEdwin, Gruber,and Padberg( 1976) and exposed in Journal of Finance.The calculation made refers to Single-Index Mode, a model result from simplification of Markowitz model, such thatthe calculation will be easier and more practical.Based on examination, it is identified that retum correlaltion among securities (particularly on stock) occurs because of response to changes in general market index. Research conducted at BES ( Surabaya Stock Market),within period of December 1999 to August 2001, using monthly data had shown that by using method of